2021
DOI: 10.1007/s10853-021-06483-z
|View full text |Cite
|
Sign up to set email alerts
|

Effects of SiC particles codeposition and ultrasound agitation on the electrocrystallisation of nickel-based composite coatings

Abstract: This study analysed the influence of the codeposition of SiC particles with different sizes: 50 nm, 500 nm and 5 μm, and the type of bath agitation (stirring or ultrasonic) on the electrocrystallisation of nickel coatings. The composites matrix microstructure was analysed by means of SEM, EBSD and XRD, to evaluate the grain size, crystal orientation, and internal stresses and was benchmarked against pure nickel samples electrodeposited in equivalent conditions. The codeposition of nano- and microsize particles… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 45 publications
0
6
0
Order By: Relevance
“…The samples from previous studies (Table 2) showed preferential crystal \100[ orientation growth independent of the current density and agitation type. They differed only in the composites containing SiC500, where random orientation growth was dominant instead of preferential crystal orientation growth [14]. The change in texture in the deposits led to a variation in the surface morphology, from a pyramidal-shaped surface observed in deposits dominated by the \100[ orientation to globularshaped structures in Ni/SiC500 composites.…”
Section: Electrodeposit Characterizationmentioning
confidence: 98%
See 4 more Smart Citations
“…The samples from previous studies (Table 2) showed preferential crystal \100[ orientation growth independent of the current density and agitation type. They differed only in the composites containing SiC500, where random orientation growth was dominant instead of preferential crystal orientation growth [14]. The change in texture in the deposits led to a variation in the surface morphology, from a pyramidal-shaped surface observed in deposits dominated by the \100[ orientation to globularshaped structures in Ni/SiC500 composites.…”
Section: Electrodeposit Characterizationmentioning
confidence: 98%
“…Sanaty-Zadeh et al [4] also observed overestimation in the theoretical calculation, reporting an increase in discrepancy in the sums of contribution method compared to others methods. The US agitation caused selective entrapment of submicron particles [14]; only the smaller particles (245 ± 55 nm average diameter) codeposited in SiC500-DC4/US. The US caused a good and uniform dispersion of particles within the matrix, resulting in an interparticle spacing of 116 ± 57 nm (Figs.…”
Section: Strengthening Mechanismsmentioning
confidence: 99%
See 3 more Smart Citations